Superstition : belief in the age of science - Park, Robert L. (Princeton, N.J. : Princeton University Press, 2008)
"From uttering a prayer before boarding a plane, to exploring past lives through hypnosis, has superstition become pervasive in contemporary culture? Robert Park, the best-selling author of Voodoo Science, argues that it has. In Superstition, Park asks why people persist in superstitious convictions long after science has shown them to be ill-founded. He takes on supernatural beliefs from religion and the afterlife to New Age spiritualism and faith-based medical claims. He examines recent controversies and concludes that science is the only way we have of understanding the world. Park sides with the forces of reason in a world of continuing and, he fears, increasing superstition. Chapter by chapter, he explains how people too easily mistake pseudoscience for science. He discusses parapsychology, homeopathy, and acupuncture; he questions the existence of souls, the foundations of intelligent design, and the power of prayer; he asks for evidence of reincarnation and astral projections; and he challenges the idea of heaven. Throughout, he demonstrates how people's blind faith, and their confidence in suspect phenomena and remedies, are manipulated for political ends. Park shows that science prevails when people stop fooling themselves. Compelling and precise, Superstition takes no hostages in its quest to provoke. In shedding light on some very sensitive - and Park would say scientifically dubious - issues, the book is sure to spark discussion and controversy"--Provided by publisher.
Lessons from a tree -- A bigger prize : in which we discover scientists of faith -- The secret of life : in which Darwin's theory of evolution by natural selection survives -- Miracle at Columbia : in which both sides pray for victory -- Giving up the ghost : in which we search for the soul -- The silent army : in which we search for an afterlife -- The tsunami God : in which the innocent suffer -- The new age : in which anything goes -- Schrödinger's grave : in which quantum mysticism is found to be superstition -- The barbary duck : in which the body heals itself -- The deer : in which the placebo effect is explained -- The moral law : in which we instinctively know right from wrong -- The last butterfly : in which there is no place else to go.
Includes bibliographical references (pages 217-219 and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Religion and science; Religion and sociology; Belief and doubt; RELIGION -- General; RELIGION -- Ethics; Belief and doubt; Religion and science; Religion and sociology; Electronic books